2020
DOI: 10.1002/imhj.21854
|View full text |Cite
|
Sign up to set email alerts
|

The contributions of child–mother attachment, maternal parenting stress, and military status to the prediction of child behavior problems

Abstract: Studies show that children with a military parent are at heightened risk of the development of behavior problems. However, there is limited work examining how other factors experienced by military families may also influence behavior problems. In the current study, we recruited three types of Canadian families with a preschooler: families with a deployed military member, families with a nondeployed military member, and nonmilitary families. We examined whether the nonmilitary parent's (in all cases the mother)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 70 publications
(102 reference statements)
1
15
0
1
Order By: Relevance
“…Results showed a significant direct effect of deployment status on attachment that was not mediated through other factors such as maternal depression, nor moderated by factors such as social support. A subsequent study (Tupper et al, 2020) examined further pathways of impact on these early attachment relationships, with a focus on maternal parenting stress. Child-mother dyads from military families (n = 51 armed forces) participated in an observed attachment assessment with the Strange Situation Procedure (SSP; Ainsworth, 2014), and mothers reported on their stress levels.…”
Section: Family Functioningmentioning
confidence: 99%
“…Results showed a significant direct effect of deployment status on attachment that was not mediated through other factors such as maternal depression, nor moderated by factors such as social support. A subsequent study (Tupper et al, 2020) examined further pathways of impact on these early attachment relationships, with a focus on maternal parenting stress. Child-mother dyads from military families (n = 51 armed forces) participated in an observed attachment assessment with the Strange Situation Procedure (SSP; Ainsworth, 2014), and mothers reported on their stress levels.…”
Section: Family Functioningmentioning
confidence: 99%
“…Van Aswegen et al also pointed to the importance of considering this maternal-child relationship in the context of problematic mother-child relationships (16). Indeed, in our previous study, we showed maternal methylation of the NR3C1 promoter region as negatively and significantly associated with parenting stress, which is a known marker of parentchild relationship disturbance and is predictive of both child internalizing (i.e., anxiety and depression) and externalizing problems (i.e., disruptive behavior disorder symptoms such as those of attention deficit hyperactivity, oppositional defiant and disruptive mood dysregulation disorder) (10,18). Parenting stress is known to be increased both in the context of maternal history of maltreatment and other interpersonal violence exposure as well as in the context of psychopathology such as PTSD and depression (19-22).…”
Section: Introductionmentioning
confidence: 93%
“…Age and gender Only one study (Crockett et al, 2020) reported on the serving military parent's mean age (33.3 years), while two studies (Crockett et al, 2020;Lester et al, 2012) reported on the non-serving military parent's mean age (35.66 years). The few studies which reported on parent gender indicated that serving military personnel were mostly males (mean: 94%; n = 2; Tupper et al, 2020;Wilson et al, 2014), and the non-serving parents were mostly females (mean: 98%; n = 4; Lester et al, 2012;Tupper et al, 2018;Tupper et al, 2020;Wilson et al 2014).…”
Section: Military Family Characteristicsmentioning
confidence: 99%